Pengaruh Pajak Daerah dan Retribusi Daerah terhadap Pertumbuhan Ekonomi Provinsi Aceh - Lutfiona Riandhani; Puti Andiny; Yani Rizal; Safuridar Safuridar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to analyze the influence of regional taxes and regional levies on economic growth in Aceh Province. The research method used is a quantitative approach using secondary data from the Central Statistics Agency (BPS) and the Directorate General of Taxes (DJP) for the period 2009–2023. Data analysis was carried out using multiple linear regression with the help of statistical software. The research results show that regional taxes. The test results show that regional taxes have a t;statistic value of 1.186951 with a probability significance test of 0.2582 where >0.05 means that regional taxes do not have a significant influence on economic growth.do not have a significant influence. significant to economic growth. On the other hand, regional levies show that regional levies have a t;statistic value of -2.988378 with a probability significance test of 0.0113 where >0.05 means that regional levies have a partially significant negative influence on economic growth. This research provides important implications for policy makers in Aceh Province in increasing the effectiveness of managing regional taxes and regional levies to encourage sustainable economic growth.